2018
DOI: 10.1038/s41467-018-03425-3
|View full text |Cite
|
Sign up to set email alerts
|

Basal lamina remodeling at the skeletal muscle stem cell niche mediates stem cell self-renewal

Abstract: A central question in stem cell biology is the relationship between stem cells and their niche. Although previous reports have uncovered how signaling molecules released by niche cells support stem cell function, the role of the extra-cellular matrix (ECM) within the niche is unclear. Here, we show that upon activation, skeletal muscle stem cells (satellite cells) induce local remodeling of the ECM and the deposition of laminin-α1 and laminin-α5 into the basal lamina of the satellite cell niche. Genetic ablati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
154
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 154 publications
(166 citation statements)
references
References 61 publications
5
154
0
7
Order By: Relevance
“…Skeletal muscle regenerative capacity is partly dictated by their ability to balance the use of stem cells for normal or exercise-induced growth and for repair with the need to preserve a pool of quiescent stem cells acting as a reservoir for future needs. The MuSC niche, composed of extra-cellular matrix and non-myogenic cells (Rayagiri et al, 2018;Wosczyna and Rando, 2018), Figure 7G). Therefore, the combined activities of the primary cilium and Hh signalling provide an exquisite mechanism to control MuSC cell cycle progression and couple it to cell fate decision.…”
Section: Discussionmentioning
confidence: 99%
“…Skeletal muscle regenerative capacity is partly dictated by their ability to balance the use of stem cells for normal or exercise-induced growth and for repair with the need to preserve a pool of quiescent stem cells acting as a reservoir for future needs. The MuSC niche, composed of extra-cellular matrix and non-myogenic cells (Rayagiri et al, 2018;Wosczyna and Rando, 2018), Figure 7G). Therefore, the combined activities of the primary cilium and Hh signalling provide an exquisite mechanism to control MuSC cell cycle progression and couple it to cell fate decision.…”
Section: Discussionmentioning
confidence: 99%
“…Knockdown of CD49f reduces differentiation potential of SSCs . Furthermore, CD49f plays an important role in the self‐renewal of PSCs, skeletal muscle stem cells, glioblastoma and breast cancer stem cells; its expression has been identified in 35 populations of stem cells . Flow cytometry data indicate that although close to 100% of cells were CD29‐positive and CD105‐positive during all 8 passages, only about 70% of PSC‐SSCs were CD49f‐positive at passage 3, and its expression decreased in subsequent passages and in cells that lost potential for proliferation and differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…First, the ECM might be an integral part of the niche that maintains the self-renewing property of MPCs. Recent work has implicated many ECM components, including fibronectin, tenascin-C, laminins and collagens, as critical niche factors that modulate satellite cell function (Bentzinger et al, 2013b;Fry et al, 2017;Rayagiri et al, 2018;Tierney et al, 2016;Urciuolo et al, 2013). In particular, it has been shown that collagen V produced by adult muscle satellite cells is an essential component of the quiescent niche, as deletion of the Col5a1 gene results in depletion of the stem cell pool (Baghdadi et al, 2018).…”
Section: Unique Features Of Col1a2 + Mpcsmentioning
confidence: 99%
“…Quiescent satellite cells often display a bipolar morphology and reside beneath the basal lamina on the surface of the myofiber (Scharner and Zammit, 2011;Webster et al, 2016). The extracellular matrix (ECM) surrounding the satellite cell constitutes its niche and has been implicated in the regulation of satellite cell behavior (Baghdadi et al, 2018;Bentzinger et al, 2013b;Fry et al, 2017;Rayagiri et al, 2018;Tierney et al, 2016;Urciuolo et al, 2013). Upon muscle injury, 'activated' satellite cells undergo proliferation and initiate the myogenic program.…”
Section: Introductionmentioning
confidence: 99%